Performance analysis of computer systems with Weibull distribution subject to software upgrade and load recovery - Kumar, Ajay; Garg, Reena; Barak, M. S. (Life cycle reliability and safety engineering, 2023)
Computer systems play an essential role in the era of science and technology, where hardware and software work together with full accuracy. In this paper, the performance of computer systems has been analyzed under hardware repair, software upgradation, and load recovery using Weibull distribution for all random variables with different scale and standard shape parameters. For this purpose, a reliability model is developed with the help of the regenerative point technique and semi-Markov approach. The system is failing due to hardware, software, or load failure. The Weibull distribution is widely used in reliability and life data analysis due to its versatility. It is assumed that all types of failure and repair rates follow the Weibull distribution, and a single repairman can attend to all kinds of failures. Numerical calculations for mean time to system failure, availability, and profit function highlight the importance of the study.